ANALISIS EFISIENSI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA USAHA TANI PADI DI KABUPATEN SUMBAWA - Illin Septi Handayani; Marisa Sutanty; I Ismawati (Jurnal Ekonomi & Bisnis, 2023)
This study aims to efficiently use the factors of production in rice farming in Sumbawa Regency. This type of research is a descriptive study to examine the production factors that have the most influence on rice farming and analyze the level of efficiency in the use of production factors in rice farming in Sumbawa Regency. The type of data used is quantitative in the form of cost and income data from rice farming. Data were obtained directly from land owner and tenant farmers in Sumbawa Regency through interviews. Steps to find outdetermine the efficiency of rice farming, the Cobb-Douglass production function analysis is used. In addition, to examine whether there is an influence of each production factor on production yields, the regression coefficient significance test is used with the t test, while the influence of the production factors used together on rice production is used the F-test. The results of this study indicate that the value of technical efficiency in the use of production factors of capital, labor and land area by owner farmers and tenant farmers in Sumbawa Regency is not efficient because the value is less than 1. The net income earned by owner farmers and tenant farmers is not optimal, because the use of the factors of production is not efficient, and it is still possible to improve this if efforts are made to use the factors of production more efficiently. Thus, rice farming for owner farmers and tenant farmers in Sumbawa Regency is still not efficient.